Interaction Effects of Nitrogen Rates and Forms Combined With and Without Zinc Supply on Plant Growth and Nutrient Uptake in Maize Seedlings - Xue, Yanfang; Yan, Wei; Gao, Yingbo; Zhang, Hui; Jiang, Liping; Qian, Xin; Cui, Zhenling; Zhang, Chunyan; Liu, Shutang; Wang, Huimin; Li, Zongxin; Liu, Kaichang (Frontiers in Plant Science, 2021)
Previous studies have shown that zinc (Zn) accumulation in shoot and grain increased as applied nitrogen (N) rate increased only when Zn supply was not limiting, suggesting a synergistic effects of N on plant Zn accumulation. However, little information is available about the effects of different mineral N sources combined with the presence or absence of Zn on the growth of both shoot and root and nutrient uptake. Maize plants were grown under sand-cultured conditions at three N forms as follows: NO3– nutrition alone, mixture of NO3–/NH4+ with molar ratio of 1:1 (recorded as mixed-N), and NH4+ nutrition alone including zero N supply as the control. These treatments were applied together without or with Zn supply. Results showed that N forms, Zn supply and their interactions exerted a significant effect on the growth of maize seedlings. Under Zn-sufficient conditions, the dry weight (DW) of shoot, root and whole plant tended to increase in the order of NH4+